Surveying the Effect of Opioid Abuse on the Extent of Coronary Artery Diseases in Diabetic Patients. (20th July 2020) - Moezi Bady, Seyyed Ali; Soltani, Maryam; Kazemi, Toba; Khosravi Bizhaem, Saeede; Hanafi Bojd, Nazanin; Partovi, Neda; Mashreghimoghadam, Hamid Reza; Hamidi, Fatemeh; Azdaki, Nahid
Abstract : Background . Diabetes mellitus is recognized as one of the most common, serious, and costly chronic diseases. Opium addiction is also a common health problem in Iran. Given the high prevalence of opium use in South Khorasan Province and the increasing prevalence of opioid abuse in the community, this study was performed to investigate the effect of opioid abuse on the extent of disease in diabetic patients undergoing coronary angiography in the cardiology department of Vali-e-Asr Hospital in Birjand city, South Khorasan Province, Iran. Methods . This study recruited a total of 1051 diabetic patients who underwent coronary angiography in the cardiology department of Vali-e-Asr Hospital of Birjand city from 2011 to 2015. The collected data were analyzed using SPSS version 22.0 with the chi-square test and univariate regression analysis. P value <0.05 was considered as statistically significant. Results . Among opiate-addicted diabetics, the risk of coronary artery disease was 0.44 times higher than among nonaddicted diabetics (range 0.24–0.77, P = 0.004 ). The extent of coronary vessel involvement, when present, was not different between the two groups. Conclusion . Opiate-addicted diabetics appear to be more susceptible to CAD than their nonaddicted counterparts. The determinants and correlates of this interaction must be the subject of further study.